Platelet activation in experimental arterial thrombosis. - Lastória, S.; Thomazini, I. A.; Cury, P. R.; Maffei, Francisco Humberto de Abreu [UNESP] (My University, 1987)
Platelet aggregates were studied in dogs with induced arterial thrombosis, by the method of Wu and Hoak. Blood was withdrawn from a jugular vein and from the femoral vein on the operated side 24 h after thrombus induction and immediately and 2 h after blood flow was restored by thrombectomy. Platelet activation was significant in dogs with obstructive arterial thrombosis and which tended to subside after thrombectomy. Activation or formation of platelet aggregates seemed to occur in the ischemic limb. It is suggested that this experimental model could be useful to test the action of anti-platelet drugs in vivo.
Keywords: animal; blood; dog; femoral artery; pathophysiology; thrombocyte aggregation; thrombosis; Animal; Dogs; Femoral Artery; Platelet Aggregation; Support, Non-U.S. Gov't; Thrombosis